Estudo experimental e computacional das propriedades vibracionais e citotóxicas de nutracêuticos do alho - Serafim, Leonardo Farias (2015)
The cytotoxic and bactericidal activities of garlic extract were tested in three tumor cell lines (HCT-166, SF-295 e OVCAR-8) and four bacteria cultures: two gram-positives (Staphylococcus aureus ATCC 25923 and Staphylococcus epidermidis ATCC 12228) and two gram-negatives (Pseudomonas aeruginosa ATCC 9027 e Escherichia coli ATCC 11303). Aiming to improve the bioavailability and cell targeting (tumor or bacteria) of these nutraceuticals, a drug delivery system based on the adsorption of garlic extract on calcium carbonate microparticles was developed. Additionally, computer simulations within the Density Functional Theory (DFT) formalism were accomplished to find the structural and vibrational properties of two molecules, alliin and methiin, present in garlic extract. alliin the highest concentration specie present in garlic extract was used as theoretical model to represent the garlic extract on the potential interaction calculations with calcium carbonate microparticles. The computer codes GAUSSIAN, Forcite and Dmol3, with the Meta hybrid M06-2X and the pure GGA-PBE Exchange-correlation functional were used to implement the computations. The vibrational spectra recorded for the alliin unveiled intense absorption peaks at: 1637, 1592, 1519, 1430, 1397, 1390, 1357 1018, 544 cm-1 on IR spectrum, mainly assigned to the carboxyl, amine and sulfoxide groups vibrations, and at 1643, 1429, 1404, 1316, 1297, 1207, 790, 744, 693, 588, 503 cm-1 on Raman spectrum, associated to the carbon chain vibrations. The methiin IR spectrum is similar to alliin’s, but, its Raman spectrum unveiled absorption bands which may differentiate both molecules, mainly for the absence of the absorption peak observed at 1643 cm-1 , ascribed to the allyl group vibration. The calculated theoretical vibrational spectra showed a good agreement with the experimental data. The interaction potential calculations suggests the adsorption of at least four solvation layers of the nutraceuticals around the calcium carbonate microparticles, this fact allow the slowly release of the species, preserving its bioavailability. The cytotoxicity tests showed tumor cells growth inhibition of 93% for the three tumor cell line studied, and bactericidal activity on gram-positives bacteria cell cultures, which proved the synergetic effect of garlic extract with calcium carbonate and its efficacy as drug delivery system. Those results shows the application potential of the calcium carbonate microparticles modified with garlic extract on the treatment of cancer and as antibacterial agent.